(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
The paper analyses the influence that the Covid-19 pandemic has had on the functioning of the European asylum system. The analysis is divided into three parts and addresses problematic issues associated with different stages of the pandemic. In the first part of the paper, the author outlines the asylum practices of EU Member States in the initial stage of the Covid-19 pandemic during which the pandemic was perceived as a state of emergency. By exploring the legal possibilities to derogate both from the EU asylum rules and international human rights standards, the author offers conclusions as regards limits of derogations and the legality of Member States’ practices, especially their failure to differentiate between rules that are susceptive of being derogated in emergency situations and those that are not. The second part of the paper analyses the current phase of the pandemic in which it is perceived as a ’new normal’ and focuses on making the EU asylum system immune to Covid-19 influence to the greatest extent possible and in line with relevant EU and human rights rules. The author insists on the vulnerability as an inherent feature of persons in need of international protection and researches upon the relationship between the two competing interests involved – protection of asylum seekers and ensuring public health as a legitimate reason for restricting certain asylum seekers’ rights. The final part of the paper analyses the prospects of the future EU asylum system, as announced by the New Pact on Migration and Asylum in September 2020, to adapt to the exigencies of both the current Covid-19 crisis and pandemics that are yet to come. With an exclusive focus on referral to Covid-19 and provisions relevant for the current and future pandemics, the author criticizes several solutions included in the instruments that make up the Pact. It is concluded that the Pact failed to offer solutions for problems experienced during the Covid-19 pandemic and that, under the pretext of public health, it prioritizes the interests of Member States over the interests of applicants for international protection.